Dual-Phase 99mTc-MIBI Imaging Findings in Sporadic Primary Hyperplasia of Parathyroid Glands. (May 2015) - Yang, Qi-Sheng; Wang, Chang-Yin; Wang, Bi-Cheng
<x xml:space="preserve">Abstract</x> Abstract Primary hyperplasia of parathyroid is uncommon and rarely documented in literatures. We report an 18-year-old female patient with hyperparathyroidism due to unifocal primary hyperplasia of parathyroid glands. Dual-phase 99mTc-MIBI imaging was performed for this patient. We found remarkably increased MIBI uptake in the hyperplastic lesion in early imaging and no extinction of the uptake in delayed imaging. These results suggest that the dual-phase 99mTc-MIBI imaging is useful in localizing the hyperfunctioning lesions of primary hyperplasia of parathyroid glands.